Wenshenyang recipe treats infertility through hormonal regulation and inflammatory responses revealed by transcriptome analysis and network pharmacology - Xie, Lan; Zhao, Shuai; Zhang, Xiaoling; Huang, Wenting; Qiao, Liansheng; Zhan, Delin; Ma, Chengmei; Gong, Wei; Dang, Honglei; Lu, Hua (Frontiers in Pharmacology, 2022)
The Wenshenyang recipe (WSYR) has the effect of treating infertility, but the mechanisms underlying this activity have not been fully elucidated. In this study, network pharmacology and RNA sequencing were combined, with database-based “dry” experiments and transcriptome analysis-based “wet” experiments used conjointly to analyse the mechanism of WSYR in the treatment of infertility. In the dry analysis, 43 active compounds in WSYR and 44 therapeutic targets were obtained through a database search, 15 infertility pathways were significantly enriched, and key targets, such as ESR1, TP53, AKT1, IL-6, and IL-10 were identified. Then the wet experiments were performed to detect the expression changes of the 412 genes from 15 infertility pathways identified by dry analysis. HK-2 cells were treated with the three herbs of WSYR and subjected to targeted RNA sequencing. Based on the results, 92 of the 412 genes in 15 infertility pathways were identified as DEGs. Additionally, key targets, such as ESR2, STAT1, STAT3, and IL6, were also identified in the wet experiments. RT-qPCR experiments further verified that WSYR played an anti-inflammatory role by upregulating IL-4 and IL-10 and Epimedium brevicornu Maxim (Yinyanghuo) showed broader effect than Drynaria fortunei (Kunze) J. Sm (Gusuibu) and Cistanche deserticola Y.C.Ma (Roucongrong). By screening compounds of WSYR using molecular docking models of ESR1 and ESR2, it was further found that xanthogalenol in Gusuibu, arachidonate in Roucongrong, and anhydroicaritin in Yinyanghuo had good affinity for estrogen receptors. These findings provide evidence for an estrogen-regulating role of the three herbs in WSYR.